Systems of organic farming in spring vetch I: Biological response of sucking insect pests (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Four systems of organic farming and a conventional farming system were studied overthe period 2012-2014. The organic system trial variants included: I – an organic farming system without any biological products used (growth under natural soil fertility) – Control; II – an organic farming system involving the use of a biological foliar fertilizer and a biological plant growth regulator (Polyversum+Biofa); III – an organic farming system in which a biological insecticide (NeemAzal T/S) was used; IV – an organic farming system including a combination of three organic products: the foliar fertilizer, the plant growth regulator and the bioinsecticide (Polyversum+Biofa+NeemAzal T/S). Variant V represented a conventional farming system in which synthetic products were used in combination (foliar fertilizer, plant growth regulator and insecticide: Masterblend+Flordimex 420+Nurelle D). Treatment of vetch plants with the biological insecticide NeemAzal in combination with Biofa and Polyversum resulted in the lowest density of sucking pests, compared to all other organic farming methods tested (i.e. without NeemAzal, with NeemAzal alone, and its combination with Biofa and Polyversum). The greatest reduction in pest numbers during the vegetation period in that variant was observed in species of the order Thysanoptera (36.0-41.4%), followed by Hemiptera, and the families Aphididae (31.6-40.3%) and Cicadellidae (27.3-28.6%). This combination showed an efficient synergistic interaction and an increase in biological efficacy as compared to individual application of NeemAzal. The highest toxic impact was found against Thrips tabaci, followed by Acyrthosiphon pisum. An analysis of variance regarding the efficacy against the species A. pisum, E. pteridis and T. tabaci showed that type of treatment had the most dominant influence and statistically significant impact.
Keywords: Organic farming; Spring vetch; Sucking insects; Biopesticides